International review of cytology - Jeon, Kwang W. (International review of cytology, 2005)
International Review of Cytology presents current advances and comprehensive reviews in cell biology - both plant and animal. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research. Articles in this volume address Plastid RNA polymerases, promoters, and transcription regulators in higher plants; Maintenance of Golgi Apparatus Structure in the Face of Continuous Protein Recycling to the ER: Making Ends Meet; Nucleocytoplasmic trafficking in plant cells; Building in vitro models of organs; Mitrochondria-drived organelles in protists and fungi; The flagellum of trypanosomes; and Regulation of growth and differentiation in Dictyostelium.